Vegetation dynamics from Lago San Martín area (Southwest Patagonia, Argentina) during the last 6,500 years - Bamonte, Florencia Paula (2015)
We report a palaeoenvironmental reconstruction since 6,650 cal. bp from the Lago San Martín area, from a peat-bog sequence, Mallín Paisano Desconocido, located at 48°58′S, 72°14′W. Between 6,650 and 4,500 cal. bp we can infer a shrub steppe dominated by Asteraceae subf. Asteroideae associated with other shrubs under relatively dry conditions, through an intensification of the westerly wind belt and a steepening in the west–east precipitation gradient. From 4,500 to 3,000 cal. bp a shrub-grass steppe development suggests a slight increase in moisture conditions although the environmental conditions remain dry. From 3,000 cal. bp a grass steppe represented by Poaceae and subordinate herbs developed, suggesting an increase in moisture availability and weaker westerly flow precipitation. The last 400 cal. bp were characterized by a change from grass to shrubby communities which could be related to the beginning of the Little Ice Age, whereas the last century shows signals of anthropic impact. The palaeoenvironmental interpretation from the Lago San Martín basin is based on moisture availability variations in relation to precipitation pattern changes of westerly origin. These trends are consistent with interpretations of records from the Andean and extra-Andean areas. The comparison with other sequences allows us to interpret the palaeoenvironmental changes in the Lago San Martín area and to integrate these variations within a regional framework, interpreting them in relation to southern past climatic changes. At a regional scale, the records show an increase in westerly intensity during the mid-Holocene, whereas weaker westerly flows are postulated for the late Holocene.